Diskursus Literasi Abad 21 di Indonesia - Dipa Nugraha; Dian Octavianah (Jurnal Pendidikan Edutama, 2020)
Abstract: This study is to describe discourse on literacy in Indonesia. This study used an extensive survey of related literature on literacy which was accessed on Google Cendekia in December 2019 using “literasi abad 21” as its keyword. The analysis is descriptive qualitative. This study concludes that: First, discourse on literacy in Indonesia started with the government’s National Literacy Movement in 2015. The discourse on literacy in Indonesia is based on New Vision for Education: Unlocking the Potential of Technology a framework for 21st century education from World Economic Forum and Boston Consulting Group, PISA 2015 Assessment and Analytical Framework from OECD, and 21st Century Skills Map from The Partnership for 21st Century Learning. Second, there are nineteen literacies discussed and developed within the discourse. However, environmental literacy and ecological literacy are absent, or at least lacking compared to the other nineteen literacies in the conversation. Considering environmental literacy and ecological literacy are both important for the future of Indonesia, it is suggested that Indonesian scholars in education should start talking more about these literacies in the conversation on literacy and their importance in Indonesian education.